Comparison of the Extraction Methods for Iron Content Assay in St. John's Wort - Fideršek, Emil Dino (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
St. John's wort is a medicinal plant that has been proven to have neurological benefits, antiviral, antibacterial, anti-inflammatory and antidepressant properties in various pharmaceutical formulations such as infusions, decoctions and extracts, owing its effects mainly to hypericin, hyperforin, tannins, and xanthones. Iron is one of the most important microelements and is essential for photosynthesis, respiration and chlorophyll synthesis. It has been shown to be an effective elicitation factor for hypericin and hyperforin production. There are several methods for the extraction of iron from plant material, including dry, wet and microwave digestion, that were described for St. John's wort. However, the extraction methods were not previously compared for their efficacy. The main goal of the research was to compare the extraction methods, namely wet and dry digestion, for the iron content assay of St. John's wort tea samples available in the Bosnian-Herzegovinian market. Three products were taken and analyzed using the thiocyanate spectrophotometric method for the determination of iron in triplicate. Both methods are practical in routine work and showed adequate sensitivity. The iron content found in samples prepared by dry digestion was 93.37 ± 17.89 mg/kg on average, while after wet digestion the iron content in the same samples was 75.7 ± 29.43 mg/kg. This is probably due to the fact that wet digestion is performed in an open system and at lower temperatures where the solubility of substances is lower. The level of iron content in St. John's wort was comparable to the literature results.